Barriers to and facilitators of hypertension management in Asmara, Eritrea: patients' perspectives - Merhawi Teklezgi Gebrezgi; Mary Jo Trepka; Eyob Azaria Kidane (BMC, 2017)
Abstract Background Personal hypertension management is a cornerstone in the prevention of hypertension complications. In Eritrea, the increase in the national life expectancy rate has been accompanied by an increase in hypertension complications such as stroke. Hence, this study was designed to identify barriers and facilitates to hypertension management from the perspective of the patients. Methods This was a qualitative study of a total of 48 individual in-depth interviews and two focus group discussions. It was conducted among hypertensive patients who were attending outpatient services at two hospitals in Asmara, Eritrea. Results This study identified barriers and facilitators of hypertension management related to the individual patient, family and community, and healthcare system. With respect to individual factors, economic barriers, stress, non-adherence to medications due to the use of traditional remedies, and difficulties and misconceptions about following physical activity guidelines were mentioned as barriers to hypertension management. Related to the community and healthcare system, low community awareness, community stigma, and inadequate health promotion materials were stated as barriers. Individual knowledge, family, and government support were reported as very important factors to the patient's success in the personal hypertension management. Conclusions Counseling patients about adherence to medication, strengthening family and government support, and empowering families and the community with appropriate knowledge of hypertension management could potentially help in an individual's adherence.